Empowering the Capacity of Housewives in Helping Emergency Cases at Home as an Effort to Fulfill Family Health Functions in RT 06 Kelurahan Baru Pasar Rebo, East Jakarta - Nipsyah Lega; Ziska Herawaty; Dira Lusi Sukmalati (PT FORMOSA CENDEKIA GLOBAL, 2022)
Errors in emergency first aid can result in fatal conditions for victims. Not infrequently the result of wrong actions when helping can increase injuries and even death. Prevention efforts in emergency situations begin with knowledge from the family, if the family has knowledge of the implementation of emergency measures it will make it easier to take the attitude of providing first aid in an emergency situation. PKM was held for 2 weeks. Implementation of activities is carried out through the provision of brief theory and practice. Participants in this community service activity are housewives in RW 06 Pasar Rebo Village, East Jakarta. The results of this activity can increase the community's knowledge and skills about the importance of emergency first aid at home. So that it can carry out the function of family health.